The complicated paths of China's rise: from the death of Lin Biao to the tragedy of Tiananmen - Alcalde Cardoza, Javier (2024)
The article analyses China´s international ascent attempting to illustrate the difficulty inherent in attempting to predict international events. The nature and consequences of China´s transformation from the 1970´s was difficult to foresee. The beginning and early stages of this process were indeed facilitated by the outcomes of internal crises of uncertain evolution as well as by key decisions of another power, the United States, guided by its own interests. The author describes some hardly visible or little expected routes taken by events that that led China, in first place, to gain access to a big export market that was instrumental for the expansion of its economy and, subsequently, made possible for its authorities to prevent, through repressive action in Tiananmen Square, that the march of reforms could provoke changes in the authoritarian nature of the state.